2005
DOI: 10.1038/sj.ijir.3901337
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a progressive treatment program for erectile dysfunction in patients with diabetes mellitus

Abstract: The aim was to evaluate the effectiveness of a progressive program, starting with simple methods and, when not effective, moving to more complex methods, to treat erectile dysfunction (ED) in patients with diabetes mellitus. A total of 284 diabetic patients with ED entered into a 6-phase program starting with sildenafil citrate (Viagra). Those with contraindications, side effects, or negative response (erection insufficient for vaginal penetration) were switched to the vacuum erection device (VED), and then pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 21 publications
(28 reference statements)
0
18
0
1
Order By: Relevance
“…In 2005, Israilov et al [38] reported on a study evaluating the effectiveness of a progressive program in ED patients with diabetes. Of those who were nonresponders or not eligible for oral treatment or who dropped out due to adverse effects, 9 of 13 (69.2%) responded to self-injection plus VED.…”
Section: Ved As Combination Therapymentioning
confidence: 99%
“…In 2005, Israilov et al [38] reported on a study evaluating the effectiveness of a progressive program in ED patients with diabetes. Of those who were nonresponders or not eligible for oral treatment or who dropped out due to adverse effects, 9 of 13 (69.2%) responded to self-injection plus VED.…”
Section: Ved As Combination Therapymentioning
confidence: 99%
“…Несмотря на то что в лите-ратуре встречаются отдельные публикации, посвя-щенные взаимосвязи ожирения и эректильной дис-функции (ЭД), нам не удалось обнаружить работ, посвященных эффективности лечения больных с эректильной дисфункцией и ожирением. Данные крупномасштабных научных исследований, посвя-щенных роли снижения массы тела в лечении других заболеваний, в частности таких, как сахарный диабет 2 типа, артериальная гипертензия, ишемическая болезнь сердца, дают основание полагать, что кон-троль массы тела и сопутствующих метаболических нарушений способны обеспечить значительное улуч-шение качества эректильной функции и эффектив-ность лечения ЭД [3,4,5,6].…”
unclassified
“…For those men who do not respond to oral PDE-5 inhibitors alone, there is some logic in combining agents (17,38), although direct evidence from randomized controlled trials is still lacking (level 1C evidence). Alternatives include vacuum-constriction devices and intracavernosal injection of vaso-active drugs (both level 1C evidence).…”
Section: Discussionmentioning
confidence: 99%
“…In the meantime, use of combination therapies in those who are nonresponsive to PDE-5 inhibitors alone appears sensible and may result in improved erections (17,38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation